Comparison of efficiency management training using lecturing and small group teaching on learning rate of Nursing and Midwifery student’s - Fariba Asgari; Taherehsadat Khoshnazar; Asiyeh Sedighi (Journal of Holistic Nursing and Midwifery)
Abstract